Translation, cross-cultural adaptation and validation of the Diabetes Empowerment Scale - Short Form - Fernanda Figueredo Chaves; Ilka Afonso Reis; Adriana Silvina Pagano; Heloísa de Carvalho Torres
ABSTRACT OBJECTIVE To translate, cross-culturally adapt and validate the Diabetes Empowerment Scale - Short Form for assessment of psychosocial self-efficacy in diabetes care within the Brazilian cultural context. METHODS Assessment of the instrument's conceptual equivalence, as well as its translation and cross-cultural adaptation were performed following international standards. The Expert Committee's assessment of the translated version was conducted through a web questionnaire developed and applied via the web tool e-Surv. The cross-culturally adapted version was used for the pre-test, which was carried out via phone call in a group of eleven health care service users diagnosed with type 2 diabetes mellitus. The pre-test results were examined by a group of experts, composed by health care consultants, applied linguists and statisticians, aiming at an adequate version of the instrument, which was subsequently used for test and retest in a sample of 100 users diagnosed with type 2 diabetes mellitus via phone call, their answers being recorded by the web tool e-Surv. Internal consistency and reproducibility of analysis were carried out within the statistical programming environment R. RESULTS Face and content validity were attained and the Brazilian Portuguese version, entitled Escala de Autoeficácia em Diabetes - Versão Curta, was established. The scale had acceptable internal consistency with Cronbach's alpha of 0.634 (95%CI 0.494- 0.737), while the correlation of the total score in the two periods was considered moderate (0.47). The intraclass correlation coefficient was 0.50. CONCLUSIONS The translated and cross-culturally adapted version of the instrument to spoken Brazilian Portuguese was considered valid and reliable to be used for assessment within the Brazilian population diagnosed with type 2 diabetes mellitus. The use of a web tool (e-Surv) for recording the Expert Committee responses as well as the responses in the validation tests proved to be a reliable, safe and innovative method.